Nanostructured materials, thin films and hard coatings for advanced applications : selected, peer reviewed papers from the 2nd International conference on nanostructured materials, thin films and hard coatings for advanced applications, Sozopol, Bulgaria, May 24-27, 2009 - Kolakieva, Lilyana; Kakanakov, Roumen (Diffusion and defect data. Solid state phenomena ;, 2010)
This special collection of peer-reviewed papers focuses on the technology, characterization and equipment required for handling nanocomposite films and hard and superhard coatings. It also covers subjects related to the development, properties and methods for the characterization of nanostructured materials for: solid-state electronics and energy technologies; nanocomposite films, hard and superhard coatings, tribological / corrosion-resistant coatings; surfaces and interfaces; nano-sensors, nanodevices and nanosystems, Equipment for deposition and characterization of nanocomposite films and industrial application of hard and superhard coatings. The book gives an overview of the state-of-the-art of nanocomposite coatings, nanostructured thin films and their applications.